A Gentrification Story - Erol,Emre (2018)
The housing question has been a core societal issue for centuries. Since Engels (1988) intervened in the debate in 1872, housing has become increasingly central as a commodity in financialised capitalism. Hong Kong has experienced some of the most problems with housing, as it has been the most unaffordable place in the world eight years in a row (Demographia, 2018). Yet, there is more than unaffordability to the housing question in Hong Kong. Gentrification theory has been an important framework to comprehend the housing problem worldwide. Whereas some gentrification scholars focus on the role of capital (supply-side explanations), others study the gentrifiers (demand-side explanations). Scholars from the Global South, particularly Hong Kong, criticise the theory’s applicability to non-Western contexts. Through examination of various statistics and field observations, findings of this thesis show that neoliberalisation of the public housing system since the mid-1990s indicates a gentrification trajectory similar to anywhere else in the world where capitalism is the main system, including the West.
Keywords: Gentrification; Hong Kong; Rent Gap Theory; Financialisaton; Public Commons